Integrasi Nilai Ulumul Hadits dalam Bimbingan dan Konseling Islam: Pendekatan Holistik di Era Modern - Syifa, Syifa; Irsydunnas, Irsydunnas (Saneskara: Journal of Social Studies, 2024)
This study examines the integration of Ulumul Hadith values in Islamic guidance and counseling services to provide holistic solutions for modern individual problems. Highlighting Hadith as the second source of Islamic teachings after the Qur'an, it explores how its values can serve as the theoretical foundation, method, and goal of counseling. Using the literature review method, this study analyzes relevant texts and frameworks to understand the integration of Ulumul Hadith values with modern psychological approaches. Key values from Hadith, such as compassion, justice, honesty, patience, and empathy, are contextualized to enhance the effectiveness and spiritual relevance of counseling practices. The findings demonstrate that integrating these values strengthens moral foundations, increases cultural and spiritual relevance, and fosters a holistic approach to addressing client issues. Practical implications for counselors are substantial, as this approach equips them to resolve problems from a deeper Islamic perspective, ensuring solutions are aligned with religious guidance. Additionally, this integration helps develop clients' personalities to be more balanced, harmonious, and aligned with Islamic principles. This study offers a model for creating spiritually grounded counseling services, addressing both psychological and moral dimensions. By combining Ulumul Hadith with modern counseling methods, the approach becomes more effective and relevant to the needs of contemporary Muslim communities.